Socialization of Voting Procedures Elections 2019 In Border Areas In Indonesia Malaysia - Susan Neni Triani; Nindy Citroresmi Prihatiningtyas; Rosmaiyadi Rosmaiyadi; Rien Anitra; Insan Suwanto; Nurul Husna; Dian Mayasari; Mardian Mardian (International Journal of Public Devotion, 2019)
The purpose of this public service activity is to provide information and knowledge to people in the border areas of the electoral procedure in 2019 which will be held in April 2019. To achieve Reviews These goals, do the "socialization of the Implementation Rules of Voting In Election 2019 Indonesia-Malaysia border in the Regions ", Socialization activities undertaken include the exposure of the material on the stages of the election 2019, 2019 election of participants, how to vote, how voting (voting) and Also the practical activities of voting ballots. These socialization activities Carried out in the village of socialization of Sekida The number of participants is about 77 persons. The results of this socialization that the activities of participants socialized mostly already understand how voting procedures, how voting (voting) and Also was Able to understand the practical activities of voting ballots. Fewer constraints faced by the participants are still a lot of participants who do not understand each other's differences ballots for representatives of the people are like District / State, Provincial Councils, Parliament, and Council.